Acute Blast Injury Reduces Brain Abeta in Two Rodent Species - De Gasperi, Rita; Gama Sosa, Miguel A.; Kim, Soong H.; Steele, John W.; Shaughness, Michael C.; Maudlin-Jeronimo, Eric; Hall, Aaron A.; DeKosky, Steven T.; McCarron, Richard M.; Nambiar, Madhusoodana P.; Gandy, Sam; Ahlers, Stephen T.; et al. (Frontiers in Neurology, 2012)
Blast-induced traumatic brain injury (TBI) has been a major cause of morbidity and mortality in the conflicts in Iraq and Afghanistan. How the primary blast wave affects the brain is not well understood. In particular, it is unclear whether blast injures the brain through mechanisms similar to those found in non-blast closed impact injuries (nbTBI). The β-amyloid (Aβ) peptide associated with the development of Alzheimer’s disease (AD) is elevated acutely following TBI in humans as well as in experimental animal models of nbTBI. We examined levels of brain Aβ following experimental blast injury using enzyme-linked immunosorbent assays for Aβ 40 and 42. In both rat and mouse models of blast injury, rather than being increased, endogenous rodent brain Aβ levels were decreased acutely following injury. Levels of the amyloid precursor protein (APP) were increased following blast exposure although there was no evidence of axonal pathology based on APP immunohistochemical staining. Unlike the findings in nbTBI animal models, levels of the β-secretase, BACE-1, and the γ-secretase component presenilin-1 were unchanged following blast exposure. These studies have implications for understanding the nature of blast injury to the brain. They also suggest that strategies aimed at lowering Aβ production may not be effective for treating acute blast injury to the brain.